2006
DOI: 10.1002/ijc.22153
|View full text |Cite
|
Sign up to set email alerts
|

What are cyclooxygenases and lipoxygenases doing in the driver's seat of carcinogenesis?

Abstract: Substantial evidence supports a functional role for cyclooxygenase- and lipoxygenase-catalyzed arachidonic and linoleic acid metabolism in cancer development. Genetic intervention studies firmly established cause-effect relations for cyclooxygenase-2, but cyclooxygenase-1 may also be involved. In addition, pharmacologic cyclooxygenase inhibition was found to suppress carcinogenesis in both experimental mouse models and several cancers in humans. Arachidonic acid-derived eicosanoid or linoleic acid-derived hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
127
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 91 publications
1
127
0
10
Order By: Relevance
“…Despite the progress achieved in cancer therapy in the last decades, the prognosis of oral SCC has not been drastically improved and the 5 years survival rate does not exceed 50% (3,4). Epidemiological data, in vitro studies in cell cultures, as well as in vivo animal studies and controlled clinical trials have demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) exert antineoplastic effects in various types of cancer, such as colon, lung, breast, prostate, and head and neck cancer (5)(6)(7)(8)(9)(10). NSAID sulindac has shown growth inhibitory and proapoptotic effects on various cancer cell lines in vitro, including colon and breast cancer cell lines (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the progress achieved in cancer therapy in the last decades, the prognosis of oral SCC has not been drastically improved and the 5 years survival rate does not exceed 50% (3,4). Epidemiological data, in vitro studies in cell cultures, as well as in vivo animal studies and controlled clinical trials have demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) exert antineoplastic effects in various types of cancer, such as colon, lung, breast, prostate, and head and neck cancer (5)(6)(7)(8)(9)(10). NSAID sulindac has shown growth inhibitory and proapoptotic effects on various cancer cell lines in vitro, including colon and breast cancer cell lines (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Cyclooxygenase 2 (COX2) is a key enzyme in the arachidonic acid metabolism involved in the biosynthesis of prostagladins, which contribute to a pro-angiogenic microenvironment in tumors. 15 Expression of COX2 is upregulated in squamous cell carcinoma and treatment with COX2 selective inhibitors results in reduced tumor growth. 16,17 Furthermore, a large body of evidence demonstrates that inhibition of COX2 enzymatic reaction results in substantial changes in the tumor-associated neo-vasculature, suggesting that COX2 could have a key role in regulating tumor-associated neoangiogenesis.…”
mentioning
confidence: 99%
“…L eukotrienes (LTs) are biologically active lipid mediators that play important roles in inflammation and are involved in pathological states with an inflammatory component, such as asthma, cardiovascular disease, or cancer (1)(2)(3)(4)(5). They derive from arachidonic acid (AA) through the action of 5-lipoxygenase (5LO) (6), an enzyme expressed in a limited number of cells, including neutrophils, eosinophils, monocytes, macrophages, mast cells, and basophils (7,8).…”
mentioning
confidence: 99%